2015
DOI: 10.1007/s40670-015-0130-x
|View full text |Cite|
|
Sign up to set email alerts
|

Radiology in the Undergraduate Medical Curriculum: Too Little, Too Late?

Abstract: There is an anecdotal need to increase radiology education in medical school. Surveys were distributed to three medical schools, with a respondency of 55 %. Over 91 % of students believed there should be more radiology teaching in medical school. Students prefer different methods of teaching, lectures, group learning, and web-based modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…This is likely, or at least in part, due to the combination of teaching methods with lectures and case based interactive sessions. Students have mentioned both anecdotally as well as in the literature that radiology teaching is lacking, which suggests that there is a large scope for improvement in the undergraduate curriculum (1)(2)(3)5). We are planning to run this course on a yearly basis to ensure that radiology teaching continues to be provided at Princess Alexandra Hospital NHS trust and provide additional numbers for continued research.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is likely, or at least in part, due to the combination of teaching methods with lectures and case based interactive sessions. Students have mentioned both anecdotally as well as in the literature that radiology teaching is lacking, which suggests that there is a large scope for improvement in the undergraduate curriculum (1)(2)(3)5). We are planning to run this course on a yearly basis to ensure that radiology teaching continues to be provided at Princess Alexandra Hospital NHS trust and provide additional numbers for continued research.…”
Section: Resultsmentioning
confidence: 99%
“…(1)(2)(3) We feel that radiology teaching is lacking in the medical school curriculum for a number of prospective reasons. Firstly, in our opinion, there appears to be a limit to the direct input that radiologists have in the medical school curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same variability is found across Europe (Ischerwood and Thomsen, ; Lass and Scheffler, ; Kourdioukova et al, ) and the United States (Gunderman et al, ; Barzansky and Etzel, ; Linaker, ). In the United Kingdom, it has been reported that junior doctors feel radiology teaching at medical school is unstructured and insufficient, ultimately resulting in them being unprepared for work (Nyhsen et al, ), with similar findings in Canada (Dmytriw et al, ) and New Zealand (Subramaniam et al, ).…”
Section: Introductionmentioning
confidence: 86%